Estimation of gestational age specific amniotic fluid index in normal pregnancy in Nepalese women (Nepal Medical College Journal, 2023)
Amniotic fluid volume (AFV) is estimated in almost all the antenatal scans referred for ultrasonography (USG). It has proven to be a very good predictor for poor pregnancy outcomes. Several standard text books have quoted normal range of amniotic fluid index (AFI). These reference range may not be applicable to all the population as over the years different studies have shown that it varies among different population. Since such variations has been postulated, our aim is to formulate a reference range of gestational age specific AFI in normal pregnancy among Nepalese women. Therefore, a cross-sectional study was carried out among 537 normal pregnancies who attended the out-patient department of Nepal Medical College Teaching Hospital. Women with any maternal and fetal complications were excluded from the study. Subsequently median, the 5th, 50th and the 95th percentile values were calculated for each gestational week and were compared with studies among other population. Among the 537 women enrolled in the study, the mean maternal age was 26.5 years with the estimated fetal weight (EFW) at term pregnancy ranged from 2372 grams to 3750 grams with the mean being 3261 grams. The mean AFI at preterm was found to be 12.6 cm ± 2.36 and at term 11.0 cm ± 2.82. The percentiles values for first to 99th percentile of the entire data was calculated and the normal range of the AFI was estimated to be between 6 – 17 cm. As studies have shown the variance in AFI range among different population. It is imperative to formulate a reference of AFI among different population. In our study we found they are lower as compared to the Caucasian population, similar to Indian population and higher than the Chinese population.